Conceptions of high school teachers on the didactic-pedagogical use of digital educational applications for the process of teaching and learning chemistry and its limitations (Research, Society and Development, 2020)
The digital technological resources help in the development of the so-called Digital Information and Communication Technologies (DICT) and are very popular, making them more and more present and accessible in everyday life. This makes these technologies promising resources for education and school education. In addition, the didactic-pedagogical use of DICT already appears as a topic for discussion in several studies and researches, and it is also cited in guiding documents for basic education, such as the Common National Curricular Base (BNCC). In the teaching of chemistry, in particular, the DICT can help teachers in the process of producing knowledge for students, since this subject is considered, by many, difficult to understand, with abstract and complex concepts. In this research, we investigate and discuss the conceptions of high school teachers about the didactic-pedagogical use of digital educational applications (Apps) in chemistry classes. For experimental data collection, we applied an electronic questionnaire for volunteer teachers. Afterwards, we compared the conceptions of these teachers to their training profile and teaching experience in the classroom. The questionnaire also asked teachers to evaluate the potential use, in the classroom, of three free educational Apps, focused on the process of teaching and learning chemistry. Eleven chemistry teachers participated in this survey, who made a positive evaluation in relation to the didactic-pedagogical use of the analyzed Apps, showing that they have potential for the process of teaching and learning chemistry. And, finally, they also brought specific positions on the limitations that still exist for this use. We consider, therefore, that all this can serve as guidelines for theoretical and practical discussions in initial and continuing teacher training courses, which seek to insert the benefits of DICT as a resource to enhance teaching.